The Role of Religiosity and Spiritual Practices as Solutions in Managing Stress - Khatijah Othman; Sapora Sipon (Universiti Sains Islam Malaysia, 2024)
Personal problem that originated from family, financial and work place affairs can be main contributors to stressful life. The way people handle it depends to the stress retention level and the way they managing the stress. Hence, to experience and having stress is considered normal to every human. However in some cases stress become too pressurize, uncontrollable and damaging. This paper is to highlight how the researching info Islamic views and practice able to materialize the Islamic way in managing stress. The roles of religiosity no doubt play an important factor in stress solution. Therefore, the focal point of discussions throughout this paper are fortifies on belief and religiosity which proven as substantial remedy in Islam. Further emphasis will be given on the role of prayer (solat) for Muslim and how does it impact on helping to cope with the stressful condition.